1978
DOI: 10.1111/j.1365-2265.1978.tb02157.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Selective Goitre Resection on Absent Thyrotrophin Response to Thyrotrophin Releasing Hormone in Idiopathic Euthyroid Goitres

Abstract: Absent thyrotrophin (TSH) response to thyrotrophin releasing hormone (TRH) was found in ten of fifty consecutive nodular goitrous patients who were clinically and biochemically euthyroid. These ten patients together with a reference group engaging fifty-eight healthy individuals matched for sex, age, and geographic region form the basis of the present study. Patients with autonomously functioning single adenomata were excluded from the investigation. In the patient group, values of serum thyroxine (T4), free T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

1979
1979
1990
1990

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Following surgical resection of autonomously secreting goitrous tissue and after recovery of adequate thyrotrophin secretion no change of the circulating thyroid hormone concentrations (Blichert-Toft et al 1978) or only a small decrease in the mean FT4-I ) were observed. In several patients the pre-operative thyroidal function may therefore reflect an actually normal or even low normal autonomous thyroid hormone secretion (during transient TSH defi¬ ciency), which may not exceed the thyroid hor¬ mone supply under normal (recovered) endo¬ genous TSH stimulation.…”
Section: Discussionmentioning
confidence: 96%
“…Following surgical resection of autonomously secreting goitrous tissue and after recovery of adequate thyrotrophin secretion no change of the circulating thyroid hormone concentrations (Blichert-Toft et al 1978) or only a small decrease in the mean FT4-I ) were observed. In several patients the pre-operative thyroidal function may therefore reflect an actually normal or even low normal autonomous thyroid hormone secretion (during transient TSH defi¬ ciency), which may not exceed the thyroid hor¬ mone supply under normal (recovered) endo¬ genous TSH stimulation.…”
Section: Discussionmentioning
confidence: 96%
“…The transient rise discovered may simply be ex¬ plained by the fact that the high normal pre¬ operative level of serum TT3 normalized after operation. It is well established that nodular goitres are able to develop varying degrees of functional autonomy resulting in preclinical hyperthyroidism with raised serum TT3 (Gemsenjäger et al 1976;Blichert-Toft et al 1978). Actually, some of our patients probably had borderline T3-thyrotoxicosis.…”
Section: Discussionmentioning
confidence: 58%
“…After selective resection of the nodular goitre the function of the pituitary-thyroid axis has been shown to be restored with normalization of serum TT3 (Blichert-Toft et al 1978). This observation may explain the hormonal changes in our study.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…As noted, the "lesion" in nontoxic nodular goiter may be diffuse. However, there are also a number of reports indicating that following the removal of a hyperfunctioning area of a nontoxic nodular goiter the previous abnormal TSH response (flat TRH-TSH) returns to normal, indicating the reestablishment of a normal TRH-TSH feedback mechanism [2]. The authors argue that with a relative autonomy of function, the only indication for thyroid hormone administration in the postoperative period is hypothyroidism.…”
mentioning
confidence: 99%